Ayurveda Treatments for Insomnia: A Narrative Review - Martina Vendrame; Victor Chai (Journal of Clinical Medicine, 2026)
Background: Sleep disorders, particularly chronic insomnia (Nidranasha), represent an escalating global public health challenge associated with extensive neuropsychological and metabolic morbidities. While conventional pharmacotherapy provides immediate symptomatic relief, concerns regarding dependency, tolerance, and altered sleep architecture necessitate the evaluation of evidence-based complementary interventions. Ayurveda offers a comprehensive multi-modality framework for sleep health through internal adaptogenic herbs (Abhyantar Chikitsa), external oil-based therapies (Bahir Parimarjana), and structured lifestyle regimens (Dinacharya/Ratricharya). This narrative literature review evaluates the current clinical and mechanistic evidence supporting Ayurvedic interventions for sleep disorders. Methods: A focused narrative review was conducted across PubMed; Scopus; Cochrane Central Register of Controlled Trials (CENTRAL); Google Scholar; and Ayurveda, Yoga and Naturopathy, Unani, Siddha and Homoeopathy (AYUSH) Research Portal for literature published between 05/01/2016 and 05/01/2026. Randomized trials, open-label and single-arm clinical studies, mechanistic and phytochemical work, and toxicological and herb–drug interaction studies were eligible. Results: Standardized Withania somnifera root extract is supported by the most rigorous data, including double-blind placebo-controlled trials with polysomnographic or actigraphic corroboration reporting reductions in sleep-onset latency and improvements in sleep efficiency. Evidence for Bacopa monnieri and Valeriana wallichii is more limited and derives largely from studies in which sleep was a secondary outcome. External therapies, notably Shirodhara and Abhyanga, are associated with favorable autonomic and electroencephalographic changes, but the available trials are small, short, and difficult to blind, and non-specific effects of warmth, touch, and therapist attention cannot be separated from any specific treatment effect. Mechanistic work implicates modulation of gamma-aminobutyric acid (GABA) signaling, hypothalamic–pituitary–adrenal signaling, and parasympathetic activation, but these findings are hypothesis-generating and derive largely from in vitro and animal models at concentrations of uncertain human relevance. Conclusions: Ayurvedic interventions show preliminary signals of benefit in insomnia, most consistently for standardized Withania somnifera, but overall certainty remains low because of risk of bias, indirect evidence, poor standardization, and an absence of long-term safety data. Current evidence supports further rigorous investigation and carefully monitored adjunctive use in selected patients rather than general integration into routine care or substitution for established treatment.